GPR data processing computer software for the PC - Lucius, Jeffrey E.; Powers, Michael H.; Geological Survey (U.S.) (Denver, Colo. : U.S. Dept. of the Interior, U.S. Geological Survey, 2002)
The computer programs presented here can perform all basic processing of GPR data, including velocity analysis and generation of CMP stacked sections and data volumes, as well as create publication quality data images.
Title from HTML title screen (viewed on June 12, 2002).
Includes bibliographical references.
Mode of access: Internet from the USGS Web site. Address as of 3-27-03: http://pubs.usgs.gov/of/2002/ofr-02-0166/ofr02%5F166.pdf; current access is available via PURL.
System requirements: Adobe Acrobat Reader (available free); DOS operating system or within a DOS window (or console) in Microsoft Windows 3.x/95/98/ME/2000; 386, 486, or Pentium Processor, a math coprocessor, and at least 4 megabytes (MB) or RAM. Sixty-four MB or more of RAM is recommended along with a large-capacity hard drive.
Keywords: Ground penetrating radar -- Software